A Palynological Study of Land Use in Medieval Mosfellsdalur, Pre-Landnám-AD1226 - Riddell, Scott J., 1967- (2014)
Since the 1960’s pollen studies have shown that Hordeum-type pollen was grown in south west Iceland in medieval times. More recently it has been inferred that cultivation in the medieval period may have been exclusive to high status farming estates e.g. Hrísbrú in Mosfellsdalur. This raises the question of whether or not cereals were cultivated on smaller farm holdings. This study sought to address this question by comparing existing pollen data from Hrísbrú, Mosfell and Leirvogstunga with new pollen data from Helgadalur and Skeggjastaðir. All are located within Mosfellsdalur and all have archaeological remains dated to c. AD 871-1226. Standard pollen counting and rapid scanning methods were applied and the chronological framework was constructed around a suite of tephra layers of known origin and date. Vegetation histories were reconstructed for Helgadalur and Skeggjastaðir that reveal the character of the environment before and after AD 871+/-2 (Landnám). Evidence was found of human activity at Skeggjastaðir immediately prior to the conventional date of settlement. Evidence also suggests a change in land use in Mosfellsdalur during the mid-12th century. More importantly, no Hordeum-type pollen was identified at either Helgadalur or Skeggjastaðir and it is concluded that cereal cultivation was the preserve of Hrísbrú (and probably Mosfell) c. AD 871-1226.